Genome-Wide Identification, Evolution, and Co-expression Network Analysis of Mitogen-Activated Protein Kinase Kinase Kinases in Brachypodium distachyon - Feng, Kewei; Liu, Fuyan; Zou, Jinwei; Xing, Guangwei; Deng, Pingchuan; Song, Weining; Tong, Wei; Nie, Xiaojun (Frontiers in Plant Science, 2016)
Mitogen-activated protein kinase (MAPK) cascades are the conserved and universal signal transduction modules in all eukaryotes, which play the vital roles in plant growth, development, and in response to multiple stresses. In this study, we used bioinformatics methods to identify 86 MAPKKK protein encoded by 73 MAPKKK genes in Brachypodium. Phylogenetic analysis of MAPKKK family from Arabidopsis, rice, and Brachypodium has classified them into three subfamilies, of which 28 belonged to MEKK, 52 to Raf, and 6 to ZIK subfamily, respectively. Conserved protein motif, exon-intron organization, and splicing intron phase in kinase domains supported the evolutionary relationships inferred from the phylogenetic analysis. And gene duplication analysis suggested the chromosomal segment duplication happened before the divergence of the rice and Brachypodium, while all of three tandem duplicated gene pairs happened after their divergence. We further demonstrated that the MAPKKKs have evolved under strong purifying selection, implying the conservation of them. The splicing transcripts expression analysis showed that the splicesome translating longest protein tended to be adopted. Furthermore, the expression analysis of BdMAPKKKs in different organs and development stages as well as heat, virus and drought stresses revealed that the MAPKKK genes were involved in various signaling pathways. And the circadian analysis suggested there were 41 MAPKKK genes in Brachypodium showing cycled expression in at least one condition, of which seven MAPKKK genes expressed in all conditions and the promoter analysis indicated these genes possessed many cis-acting regulatory elements involved in circadian and light response. Finally, the co-expression network of MAPK, MAPKK, and MAPKKK in Brachypodium was constructed using 144 microarray and RNA-seq datasets, and ten potential MAPK cascades pathway were predicted. To conclude, our study provided the important information for evolutionary and functional characterization of MAPKKK family in Brachypodium, which will facilitate the functional analysis of BdMAPKKK genes, and also will facilitate better understanding the MAPK signal pathway in Brachypodium and beyond.